Krolewna Sniezka i siedmiu krasnoludkow - Busquets, Carlos; Jarmolkiewicz, Elzbieta (Zielona Gora : E. Jarmolkiewicz, 1994)
An adaptation of the story of Snow White and the Seven Dwarfs, for young children. Ages 4-7.